1985
DOI: 10.1098/rspa.1985.0014
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical analysis of the isothermal elastohydrodynamic lubrication of concentrated contacts. I. Direction of lubricant entrainment coincident with the major axis of the Hertzian contact ellipse

Abstract: Engineers have known since the last century that a substantial film of lubricant must be present at the contact between gear teeth. However, it is only in the last twenty-five years that analytical techniques have developed to the extent where theoretical predictions of film thickness are in accord with experience. This has come about through the in­ corporation in analysis of the effects of elastic distortion of the solids and the enhancement of lubricant viscosity due to pressure. Formulae for the prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(56 citation statements)
references
References 2 publications
4
52
0
Order By: Relevance
“…This situation, together with the fact that high pressure rheological measurements are difficult and expensive, led to the extrapolation of the pressureviscosity coefficient from film thickness measurements. [27] and Hamrock et al [28] presented the best fitting (R 2 4 97%) for the lubricant with known a-value. Van Leeuwen also calculated the pressureviscosity coefficient of the other base oil, using these equations and the film thickness measurements.…”
Section: Pressure-viscosity Coefficientmentioning
confidence: 99%
“…This situation, together with the fact that high pressure rheological measurements are difficult and expensive, led to the extrapolation of the pressureviscosity coefficient from film thickness measurements. [27] and Hamrock et al [28] presented the best fitting (R 2 4 97%) for the lubricant with known a-value. Van Leeuwen also calculated the pressureviscosity coefficient of the other base oil, using these equations and the film thickness measurements.…”
Section: Pressure-viscosity Coefficientmentioning
confidence: 99%
“…These were then adjusted to predict the film thicknesses in the MTM friction tests by taking account of the stiffer materials (WC), smaller ball radius and differing loads in the latter using the Dowson and Chittenden EHD point contact equation [29]. This showed that all subsequent MTM friction measurements were made at a lambda ratio (ratio of central film thickness to composite surface roughness) of greater than 1.8, and in most cases greater than 2.5.…”
Section: Ehd Film Thicknessmentioning
confidence: 99%
“…Replacing for the central oil film thickness from Chittenden-Dowson [4], Eq. (18) can be rewritten as: …”
Section: Inlet Zone Thermal Analysismentioning
confidence: 99%
“…A typical EHD contact comprises three distinct regions: (1) the inlet region, where the lubricant is entrained into the contact and rapid buildup of pressure occurs; (2) the central (high-pressure) contact region, where the lubricant film acts like a glassy solid with high viscosity and an almost uniform film thickness; and (3) the outlet region, where a sharp negative pressure gradient leads to lubricant film rupture and cavitation. Initial predictive analyses assumed lubricant viscosity in the inlet region to be the same as its dynamic atmospheric bulk value [3][4][5][6]. Invariably, this assumption can lead to an overestimation of lubricant film thickness.…”
Section: Introductionmentioning
confidence: 99%